2021
DOI: 10.3390/wevj12010025
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Analysis of Social Acceptance Regarding Electric Vehicles with a Focus on Charging Infrastructure and Driving Range in Germany

Abstract: A variety of measures are currently being taken on both the national and international levels in order to mitigate the negative effects of climate change. The promotion of electric mobility is one such measure for the transport sector. As a key component in a more environmentally-friendly, resource-saving, and efficient transport sector, electric mobility promises to create better sustainability. Several challenges still need to be met to exploit its full potential. This requires adapting the car technology, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Aside from the availability, the complexity of planning a charging infrastructure for EVs should be considered. The factors to be considered may include the target group, geographical characteristics of a region, type of charging station, access, payment, pricing modalities, and roaming [90].…”
Section: Barriers To Sustainable Public Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the availability, the complexity of planning a charging infrastructure for EVs should be considered. The factors to be considered may include the target group, geographical characteristics of a region, type of charging station, access, payment, pricing modalities, and roaming [90].…”
Section: Barriers To Sustainable Public Transportmentioning
confidence: 99%
“…The results identified that social acceptance, government laws on the development, purchase, and use of EVs, as well as the implementation of government policies are the top drivers. Public opinion or social acceptance is indispensable to the successful establishment of electric mobility in the automotive market [90]. In the case of the Philippines, PUV drivers and commuters preferred to drive/ride due to its modern features such as air-conditioning, non-contact payment, availability of Wi-Fi and USB port, navigation, and more comfortable ride.…”
Section: Drivers To Sustainable Public Transportmentioning
confidence: 99%
“…With the introduction of the LCEV (Low Carbon Emission Vehicle), it is anticipated that this program will contribute to the achievement of the goal of 20 percent of environmentally friendly cars in total vehicle production by 2025. Although there are numerous obstacles to overcome, some of the most significant are those related to public acceptance of electrified vehicles, driving comfort, energy charging infrastructure electricity, domestic supply chains, adoption of technology and regulatory frameworks, as well as support for fiscal and non-fiscal policies (Burkert et al, 2021). Aim: To make it possible for the general population to use electric cars without incurring prohibitively large extra expenses.…”
Section: Policy On Vehiclementioning
confidence: 99%
“…This number may be taken as a rough guideline, as in real world applications, other terms, such as the availability of a charging infrastructure [10] and prices for competing transport solutions [8,11], are also important. All of these criteria strongly affect the social acceptance of electric vehicles, as shown by Burkert et al [12] in their analysis of Germany from 2011 to 2020.…”
Section: Introductionmentioning
confidence: 96%